The influence of the financial crisis on corporate voluntary disclosure: some Malaysian evidence - Ahmed Haji, Abdifatah; Mohd Ghazali, Nazli Anum (Palgrave Macmillan, 2012)
This article examines voluntary disclosure in the annual reports of 85 Malaysian companies listed on Bursa Malaysia. In departure from prior studies, which mainly examined the impact of social or environmental accidents on corporate disclosure, we examined voluntary disclosures for two years, 2006 and 2009, in an attempt to determine whether the 2007/08 financial crisis had some impact on corporate voluntary disclosure (CVD). Drawing on proprietary costs theory, we argued that in times of financial crisis companies might not have afforded the costly process of additional voluntary disclosures due to the related preparation and competitive costs. Hence, companies would have provided less voluntary information after the financial crisis. On the other hand, the financial crisis might have forced companies to be involved in more social activities to legitimize their existence. It could be argued that the public was in greater need during the financial crisis, and hence their expectations from company contributions might have been higher. To reduce the possibility of ‘legitimacy gap’, companies may have increased their involvement in corporate social responsibility (CSR) Programs, which in turn led to increased corporate disclosure. Using a self-constructed disclosure checklist, the findings of the study indicate that the extent and quality of CVDs provided in the annual reports of sample companies increased significantly following the recent global financial crisis. The results also reveal that based on the category of information (that is, strategic, financial, CSR), CSR information was the most widely disclosed category following the financial crisis. These findings support the view that companies utilize their annual report voluntary disclosures as a means of influencing society's perception of their operations, and as a means of legitimizing their existence.